Impact of Halal Information on Purchasing Decisions moderated Religiosity in Food and Beverage Provision - Junaidin Junaidin; Syarifah Hudaya; Laode Rijai; Tetra Hidayat; Djoko Setyadi (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
Halal information on Food and Beverage Preparations, analyze for influence on Purchasing Decisions. Novelty research is the Role of Moderation to the relationship of Halal Information to Purchasing Decisions. Using structural model equations (SEM), there is a positive and significant impact of Halal Information on Purchasing Decisions. There is a positive and considerable moderation of Religiosity to the relationship between Halal Information and Purchasing Decisions. The practical implications of the study's results, empirically proving that Halal Information listed on Food and Beverage Preparations led to an increase in Purchasing Decisions, and consumer Religiosity showed significant differences. Advice for Food and Beverage manufacturers to keep halal information on Food and Beverage Preparations because it affects positive buying decisions.